2336 Novel PGF2a synthesis pathway in epithelial ovarian cancer. (21st November 2018) - Hu, Muhan; Tiwary, Ekta; Arend, Rebecca; Miller, Michael
Abstract : OBJECTIVES/SPECIFIC AIMS: To understand the role of PGF2a and to characterize a novel cyclooxyrgenase (COX)-independent prostaglandin synthesis pathway in epithelial ovarian cancer. METHODS/STUDY POPULATION: We used high grade epithelial ovarian cancer cell line (OVCAR3) as a model to study our pathway. Our main mode of PGF2a detection is through mass spectrometry. RESULTS/ANTICIPATED RESULTS: Our current results suggest the OVCAR3 cells may synthesize PGF2a independently of COX enzymes. We anticipate this novel pathway may be dependent on the TGFb pathway. DISCUSSION/SIGNIFICANCE OF IMPACT: Understanding the role and synthesis pathway of PGF2a may allow us to uncover a novel therapeutic pathway for high grade ovarian cancer.